Edukasi Peningkatan Pelestarian Konservasi Penyu Melalui Permainan Lego Bricks di Desa Apar Kota Pariaman - Basyarul Aziz; Azlin Resiana (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
The conservation of sea turtles in Desa Apar, Kota Pariaman, faces serious challenges due to the illegal trade of turtle eggs, bycatch in fishing activities, and disturbances from the tourism sector, leading to a decline in turtle populations. To raise public awareness of turtle conservation, an education program was implemented using Lego Bricks with a Participatory Rural Appraisal (PRA) approach. This method allows participants to actively identify environmental issues, understand the life cycle of turtles, and design community-based conservation solutions. The results showed an increase in participants' understanding from 45% before the education to 75% after, with 70% committing not to consume turtle eggs anymore, while 60% expressed interest in participating in sustainable conservation activities such as beach patrols and habitat rehabilitation. This game-based approach also encouraged the formation of volunteer communities focused on turtle protection and the development of conservation-based ecotourism as a more sustainable economic alternative. Education that combines interactive and participatory methods has proven effective in raising environmental awareness and fostering a collective sense of responsibility. With continuous support from various stakeholders, this approach can serve as a conservation education model applicable to other coastal areas.